2020
DOI: 10.1016/j.jelekin.2019.102379
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and muscle activity when running in partial minimalist, traditional, and maximalist shoes

Abstract: Ultra-cushioning (ULTRA) shoes are relatively new to the running shoe market. While several studies have evaluated joint kinematics and kinetics when running in ULTRA shoes, to date it remains unknown how such shoes influence joint coordination. Therefore the purpose of this study was to evaluate lower extremity coordination and coordination variability when running in minimalist (MIN), traditional (NEUT) and ULTRA shoes. Fifteen recreational runners ran for ten minutes in each shoe type. Lower extremity coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In relation to the neuromuscular variables, we found no significant changes in the neuromuscular variables between shoe mass conditions, similar to the results of Divert et al (2008). The differences in leg stiffness are primarily due to reduced contact time (Morin et al, 2007) produced by increased ground impact forces (Pollard et al, 2018) and muscle activity (Becker and Borgia, 2020). A possible explanation for the lack of changes in Kleg and Kvert could be that there were no contact time differences between shoe conditions (p = 0.642; η 2 = 0.004).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In relation to the neuromuscular variables, we found no significant changes in the neuromuscular variables between shoe mass conditions, similar to the results of Divert et al (2008). The differences in leg stiffness are primarily due to reduced contact time (Morin et al, 2007) produced by increased ground impact forces (Pollard et al, 2018) and muscle activity (Becker and Borgia, 2020). A possible explanation for the lack of changes in Kleg and Kvert could be that there were no contact time differences between shoe conditions (p = 0.642; η 2 = 0.004).…”
Section: Discussionsupporting
confidence: 77%
“…Regarding the kinematic results of our study, these data are in line with previous research. Minimalist shoes (Fuller et al, 2016) and heavier shoes (Becker and Borgia, 2020) have small acute effects on stride length and frequency compared to conventional shoes. In our study, we found non-significant stride length changes associated to the added mass (p = 0.097; η 2 = 0.016).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study found that in the time of peak activity of the lateral gastrocnemius, running with heavy shoes significantly delayed the gait cycle by approximately 4% [ 23 ]. However, J Becker, BJJoE Borgia and Kinesiology [ 24 ] found no difference in lateral gastrocnemius muscle activation during the whole gait cycle. In this study, differences were found in the braking phase, which may indicate that different shoe weights can change muscle activation during the braking phase.…”
Section: Discussionmentioning
confidence: 99%
“…Whether and how the neuromuscular system modifies the activity of leg muscles in response to different running (footwear) conditions has been the focus of many investigations. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 In such standard footwear assessment protocols, runners are asked to test a range of different and randomly presented running shoes in separate bouts of constant-speed running. While the majority of investigators have applied the same experimental technique to investigate muscle activation patterns, i.e., surface electromyography (EMG), the experimental designs have varied greatly between studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most experimental protocols try to avoid fatigue by avoiding prolonged running; instead, they examine muscle activation patterns during separate running bouts for each condition of interest, with intermittent rest periods between them. 8 , 10 , 12 , 14 , 15 Therefore, it is necessary to characterize how leg muscle activity adapts to a standard protocol intended for the comparison of different running (footwear) conditions and to determine whether or when a steady state can be reached.…”
Section: Introductionmentioning
confidence: 99%